Effect of steel fiber and carbon black on the self-sensing ability of concrete cracks under bending - Ding, Y. (2019)
fiber (SF), carbon black (CB) and carbon fiber (CF), when subjected to bending. The effect of the utilization of multiphase conductive materials on the compressive strength of the concrete and the load - deflection - fractional change in impedance (FCI) relationship of the concrete beam are investigated. The relationships between FCI and crack opening displacement (COD) and sensitivity (gauge factor) are also studied. Moreover, the quantitative analysis of signal noise in FCI-COD curves has been accomplished by the fractal geometry method. The result shows that a monotonic linearity and bi-linearity increasing relationship between FCI and COD can be observed for beams with deflection-softening (Group A and Group B specimens) and deflection-hardening (Group C specimens) behavior, respectively. The diphasic conductive admixture (SF + CB) improves the FCI-COD curve with higher sensitivity and lower noise signal compared to the monophasic conductive admixture (SF) and the triphasic conductive admixture (SF + CB + CF) specimen.